The impact of intellectual deviation on social security ( A Field study in Tishreen University ) - Alali, Adil; Kherbek, Ghaith (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
In light of the existing events, social institutions lead to a major role in preventing the intellectual and behavioral deviations of a large number of university youth. The facts indicate that the conflict between countries began to take on an intellectual character, with each party invading ideas and distorting them through various means: cultural or informational in order to challenge the principles and ethics of the other party and weaken its capabilities, dispersing its efforts and provoking strife and suspicions and questioning its principles, values and the replacement of alternative concepts, values and ideas with perverse principles that lead in one way or another to the intellectual and social collapse of society. The present study deals with the impact of intellectual deviation on the social security of the society. To achieve the objectives of the research, a questionnaire was designed and administered to a sample of students of the Department of Sociology, the fourth year Sociology Students in Tishreen University, reaching 61 students. The Search yielded the following results: - The study revealed the extent of the awareness of the sample members of the role of social institutions in the prevention of intellectual deviation. - The study showed that the various manifestations of intellectual deviation lead to destabilizing the social security of society.